Treatment of coking wastewater in a heterogeneous electro-Fenton system: Optimization of treatment parameters, characterization, and removal mechanism. (February 2022) - Meng, Guangcai; Jiang, Nan; Wang, Yanqiu; Zhang, Huan; Tang, Yin; Lv, Yanli; Bai, Jinfeng
Abstract: Coking wastewater is a typical refractory industrial wastewater with complex hazardous materials and high organic content. A novel heterogeneous electro-Fenton system with a homemade iron-loaded activated carbon cathode was used to treat coking wastewater. Based on response surface methodology, chemical oxygen demand (COD) and ammonia nitrogen (NH3 -N) were used as research indicators for the optimization of the reaction parameters. Under the optimal conditions of 1 cm electrode spacing, 10 V applied voltage, and initial pH of 3.88, the COD removal rate in several experiments was 88.91–96.65%, and the NH3 -N removal rate in several experimental runs was up to 100%. We used ultraviolet-visible spectroscopy, Fourier-transform infrared spectroscopy, three-dimensional excitation-emission matrix fluorescence, gas chromatography–mass spectrometry, and color analysis for analyses; and found that the cyclic aromatic compounds and hazardous materials containing unsaturated double and triple bonds could be effectively degraded by the modified electro-Fenton method. Additionally, the color of the coking wastewater can also be effectively removed using this technique. The studied mechanisms and UV254 analysis illustrated that the modified electro-Fenton method can effectively degrade COD and NH3 -N, remove most hazardous materials, and improve the biodegradability of coking wastewater. Graphical abstract: Unlabelled Image Highlights: A novel electro-Fenton was used to treat coking wastewater by Fe/AC/Ni cathode. The best NH3 -N and COD removal rate can reach 100% and 96.65%, respectively. No secondary pollution occurs in the whole electro-Fenton process. The biodegradability of the wastewater is significantly improved after treatment.